Race to the Pole - Cracknell, James; Fogle, Ben (London Pan Books, 2010)
A very British adventure: The first race to the South Pole since Scott and Amundsen, 100 years ago.
Include Color Illustrations.
Keywords: Adventure and adventurers -- Antarctica -- Travel